ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Pada Perusahaan Property Real and Estate yang terdaftar di BEI) - Faricha, Afrida Nur; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTOne of the characteristics of qualitative in presenting the financial statement is relevant, it can be seen from the timeliness of presenting the report. The timeliness can be seen from audit delay which is the length of time between the date of close book until the date of auditor statement. This research is meant to examine empirically the influence of firm size, profitability, solvability, firm complexity, public accountant firm size, and audit opinion to the audit delay. The research object is Property Real and Estate companies which are listed in Indonesia Stock Exchange in 2012-2015 periods. The sample collection technique has been carried out by using purposive sampling and the predetermined criteria, 28 companies have been selected as samples . The data has been done by using financial statement which has been published in the official website of www.idx.co.id. The data analysis technique has been carried out by using descriptive statistic, classic assumption test, and multiple regressions analysis.The result of this research has proved that the average of audit delay occurs in 81 days. The result of partial test shows that the variableswhich give influence to the audit delay i.e. profitability, PAF size, and audit opinion, whereas the variables of firm size, solvency and firm complexity do not give any influence to the audit delay. The result of simultaneously test has concluded that all independent variables give influence to the dependent variable.Keywords: Audit delay, firm size, profitability, audit opinion.